(3edNU bhGYO GddZI GdYQHjIs (3eQLY cGed dbhGYO GdfMh hGdUQa CYO HCSdhH Tjb heHJcQ hHUhQI eHSWI SgdI heQJHI eY GdJhVjM HGdCeKdI hGdLOGhd (B/s - (3fYeI, aDGOs ((3GdbGgQI (B:s (3fgVI eUQ ddWHGYI hGdfTQ hGdJhRjY,s)
(3bhGYO GdfMh(B.s
(3jTJed Ydi edGMb(B.s
(3jMJhj Ydi edGMb(B.s
Keywords: (3GddZI GdYQHjIs -- (3fMhs -- (3OQGSI hJYdjes; (3GddZI GdYQHjIs -- (3UQas -- (3OQGSI hJYdjes